1997
DOI: 10.1016/s0042-6989(96)00207-6
|View full text |Cite
|
Sign up to set email alerts
|

Motion-reversal Reveals Two Motion Mechanisms Functioning in Scotopic Vision

Abstract: We studied scotopic motion mechanisms, using a two-frame sinusoidal grating separated by various ISIs equated for mean luminance level. Perceived direction of displacement varied with both ISI and luminance. As luminance decreased, apparent motion reversal disappeared. This is predicted by a first-order motion model if the underlying temporal impulse response function varies from biphasic under photopic conditions to monophasic under scotopic conditions. Performance at long (but not short) ISIs depends upon st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
42
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 53 publications
10
42
0
Order By: Relevance
“…It should be noted that this idea does not exclude the possibility that the energy-based sensor is also sensitive to a lower velocity. In contrast, higher-order motion mechanisms such as an attentional tracking mechanism are insensitive to higher velocity and lower contrast (Adelson & Bergen, 1985;Burr, Ross, & Morrone, 1986;Burr & Thompson, 2011;Cavanagh, 1992Cavanagh, , 1994Cavanagh & Alvarez, 2005;Del Viva & Morrone, 1998;Derrington, Allen, & Delicato, 2004;Lu & Sperling, 1995Nishida, 2011;Smith, Hess, & Baker, 1994;Takeuchi & De Valois, 1997Verstraten, Cavanagh, & Labianca, 2000). Based on these previous studies, we assumed that a low-level motion mechanism such as the first-order motion mechanism would be responsible for the induction of negative priming.…”
Section: Characteristics Of Visual Motion Priming and Its Relation Tomentioning
confidence: 98%
See 1 more Smart Citation
“…It should be noted that this idea does not exclude the possibility that the energy-based sensor is also sensitive to a lower velocity. In contrast, higher-order motion mechanisms such as an attentional tracking mechanism are insensitive to higher velocity and lower contrast (Adelson & Bergen, 1985;Burr, Ross, & Morrone, 1986;Burr & Thompson, 2011;Cavanagh, 1992Cavanagh, , 1994Cavanagh & Alvarez, 2005;Del Viva & Morrone, 1998;Derrington, Allen, & Delicato, 2004;Lu & Sperling, 1995Nishida, 2011;Smith, Hess, & Baker, 1994;Takeuchi & De Valois, 1997Verstraten, Cavanagh, & Labianca, 2000). Based on these previous studies, we assumed that a low-level motion mechanism such as the first-order motion mechanism would be responsible for the induction of negative priming.…”
Section: Characteristics Of Visual Motion Priming and Its Relation Tomentioning
confidence: 98%
“…Human motion perception indeed changes as light intensity decreases. Velocity perception (Gegenfurtner, Mayser, & Sharpe, 2000;Hammett, Champion, Thompson, & Morland, 2007;Pritchard & Hammett, 2012;Vaziri-Pashkam & Cavanagh, 2008), velocity discrimination thresholds (Takeuchi & De Valois, 2000), short-range motion perception (Dawson & Di Lollo, 1990), complex-motion perception (Billino, Bremmer, & Gegenfurtner, 2008), biological-motion perception (Billino et al, 2008;Grossman & Blake, 1999), perception of static-motion illusions (Hisakata & Murakami, 2008), perception of interstimulus interval (ISI) reversal (Sheliga, Chen, FitzGibbon, & Miles, 2006;Takeuchi & De Valois, 1997Takeuchi, De Valois, & Motoyoshi, 2001), perception of two-stroke motion (Challinor & Mather, 2010;Mather & Challinor, 2009), the coherent-motion threshold (Billino et al, 2008;Lankheet, van Doorn, & van de Grind, 2002;van de Grind, Koenderink, & van Doorn, 2000), moving texture segregation (Takeuchi, Yokosawa, & De Valois, 2004), and visual motion priming (Takeuchi, Tuladhar, & Yoshimoto, 2011;Yoshimoto & Takeuchi, 2013) have all been shown to vary with the light level.…”
Section: Introductionmentioning
confidence: 99%
“…for the slow temporal filter and 6 for the fast temporal filter, as used in previous modelling (Emerson et al 1992;Strout et al 1994;Takeuchi et al 1997;Bergen and Wilson 1985;Rushton 1962). The parameter β reflects the weighting of the negative phase of the temporal impulse response relative to the first positive phase and was set to 0.9 (Strout et al 1994;Takeuchi and De Valois 1997;Fuortes and Hodgkin 1964).…”
Section: Motion Energy Modelmentioning
confidence: 99%
“…The parameter β reflects the weighting of the negative phase of the temporal impulse response relative to the first positive phase and was set to 0.9 (Strout et al 1994;Takeuchi and De Valois 1997;Fuortes and Hodgkin 1964). The product of the even and odd spatial profiles [i.e.,…”
Section: Motion Energy Modelmentioning
confidence: 99%
“…in roddominated vision) and have demonstrated that motion perception is affected in scotopic light level [18,19,20,22,23,24,25,26,27]. However, the rod disadvantage in motion perception seemed to rely on the difficulty in extracting temporal changes.…”
Section: Introductionmentioning
confidence: 99%